Sliding mode control with linear quadratic hyperplane design : an application to an active magnetic bearing system - Husain, Abdul Rashid (Institute of Electrical and Electronics Engineering (IEEE), 2007)
This paper deals with modeling and control of a nonlinear horizontal active magnetic bearing (AMB) system via current control scheme. The gyroscopic effect and mass imbalance inherited in the system are proportional to the rotor speed in which these nonlinearities cause high system instability as the rotational speed increases. In order to synthesize a robust controller that can stabilize the system under a wide range of rotational speed, the dynamic AMB model is transformed into a deterministic model to form a class of uncertain system. Then, based on Sliding Mode Control (SMC) theory and Lyapunov method, a new robust controller that stabilizes the system is proposed wherein the Linear Quadratic Regulator (LQR) is used to design the sliding surface. Under this control, the reaching condition is guaranteed and the closed loop system is stable. The performance of the controller applied to the AMB model is demonstrated through simulation works under various rotational speeds and system conditions.